COMPARISON OF IMPLEMENTATION BETWEEN EMA, WMA, SMA IN PREDICTING IHSG - Ahmad Dwikhaldi Rifai; Tio Adi Kurniawan; Agus Iskandar (Adisam Publisher, 2024)
This study compares the implementation of Exponential Moving Average, Weighted Moving Average , and Simple Moving Average in the movement of the Composite Stock Price Index. Through the analysis of historical IHSG data, we found that EMA consistently outperforms WMA and SMA with higher accuracy. This result indicates that the use of EMA, focusing on recent data, can be a more responsive approach to changes in stock market trends. However, this research also highlights the need to consider the weaknesses and limitations of each forecasting method. The implications of these findings can provide valuable guidance for stock market practitioners in investment decision-making. Future research can deepen this analysis by considering additional factors to improve IHSG predictions